DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP PERKEMBANGAN KARAKTER SISWA DI ERA DIGITAL PADA PESERTA DIDIK DI SDN BUGEL 4 - Apriliyani, Elsa; Mujazi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social media is a technology that is often used by people as a means of communication. One of the social media that is often accessed is TikTok. TikTok displays many interesting features, one of which is providing information that is free and can be accessed by anyone and anywhere. Many TikTok users are young and old, even elementary school students. This research aims to explain the results of the analysis of the impact of using TikTok social media on the character development of students at SDN Bugel 4, both positive and negative impacts. This type of research is qualitative using descriptive methods. Data collection techniques use interviews, observation, documentation, and questionnaires. The respondents in this research were 10 students. The results of this research show that, 1) Students use TikTok social media more than 8 hours a day, both for entertainment and for learning. 2) The use of TikTok social media by students has positive and negative impacts. The positive impacts include TikTok being a source of entertainment for students after studying, adding new insights, critical thinking, honing creativity, and helping students get the latest information about things they are interested in. On the other hand, negative impacts include students' tendency to follow unfavorable trends, such as using harsh language, verbal bullying, spending excessive time on TikTok, being less social and ignoring their surroundings, and experiencing addictions that interfere with various daily activities.